2015
DOI: 10.1590/1806-9282.61.03.275
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs, cancer and ionizing radiation: Where are we?

Abstract: Conflict of interest: noneThe aim of this study is to describe the biogenesis of microRNA, its relations with carcinogenesis, and the correlation between microRNA and ionizing radiation (IR), focusing on radioresponsiveness. It is known that microRNA biogenesis is well established and involves different enzymatic cleavages, resulting in the production of mature microRNA. MicroRNAs are involved in carcinogenesis. Their interaction is related to the genetic and epigenetic changes associated with activation of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…20 On the molecular level, radiation-induced damage initiates a complex signaling cascade in cells, resulting in a variety of responses that include cell cycle arrest, induction of stress-response genes, DNA repair, and apoptosis. 21 IR damage activates a number of stress-response-signaling pathways that contribute to lethality, and many of these may be independent of DNA damage. 20, 21 Radiation can also up or downregulate miRNA expression, and such alteration of miRNA expression profiles could affect the final outcome of radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 On the molecular level, radiation-induced damage initiates a complex signaling cascade in cells, resulting in a variety of responses that include cell cycle arrest, induction of stress-response genes, DNA repair, and apoptosis. 21 IR damage activates a number of stress-response-signaling pathways that contribute to lethality, and many of these may be independent of DNA damage. 20, 21 Radiation can also up or downregulate miRNA expression, and such alteration of miRNA expression profiles could affect the final outcome of radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…21 IR damage activates a number of stress-response-signaling pathways that contribute to lethality, and many of these may be independent of DNA damage. 20, 21 Radiation can also up or downregulate miRNA expression, and such alteration of miRNA expression profiles could affect the final outcome of radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(103, 104). Proton and gamma irradiation each result in unique changes in transcriptome regulation (105), gene methylation (106) and miRNA biogenesis (107, 108). Using protons and gamma sources, investigators at the Tufts University School of Medicine showed opposite angiogenic responses (L. Hlatky).…”
Section: Introductionmentioning
confidence: 99%
“…Further, miR-34a, which is upregulated after exposure to IR or etoposide, is another p53 target. miR-34a functions downstream of the p53 pathway as a tumor suppressor and is involved in regulating cell cycle arrest and apoptosis [106,107]. In addition to miR-34, it is well established that miR-21 targets many genes (Cdc25A, pAKt, PTEN) in the cell cycle arrest, DDR, and apoptotic pathways, and is consistently upregulated upon IR in a variety of normal and cancer cell lines [108,109].…”
Section: Mirna’s Therapeutic Function In Cancer Based On Its Regulmentioning
confidence: 99%